Isolation of Rat and Human Hippocampal Neuron Fractions in a Discontinuous Density Gradient - John Graham (The Scientific World Journal)
The plating efficiency of neurons in culture is highly dependent on the concentration of cells used to establish the monolayer. A discontinuous iodixanol gradient permits both the production of a viable concentrated suspension of neurons and purification from other brain tissue elements. The gradient that is described in this Protocol Article is applicable to brain tissue from rat and also from human biopsy specimens.